HYDROGEN PRODUCTION USING A THERMOCHEMICAL CYCLE - Avsec, Jurij; Novosel, Urška; Strušnik, Dušan (Journal of Energy Technology, 2023)
Sustainable methods of clean fuel production are needed throughout the world due to depleting oil reserves and the need to reduce carbon dioxide emissions. The technology based on fuel cells for electricity production or the transport sector has already been developed. However, a key missing element is a large-scale method of hydrogen production. The copper-chlorine (CuCI) combined thermochemical cycle is a promising thermochemical cycle that can produce large amounts of cheap hydrogen. A particularly promising part of this process is its use in combination with nuclear or thermal power plants. This paper focuses on a CuCl cycle and describes the models used to calculate thermodynamic and transport properties. This paper discusses the mathematical model for computing the thermodynamic properties for pure HCl and CuCl2. The mathematical model developed for the solid phase takes into account vibrations of atoms in molecules and intermolecular forces. This mathematical model can be used for the calculation of the thermodynamic properties of polyatomic crystals on the basis of the Einstein and Debye equations. The authors of this paper developed the model in the low temperature and high temperature region. All the analytical data have been compared with some experimental results and show a relatively good match. For the solid phase, the authors developed a model to calculate thermal conductivity based on electron and phonon contributions.